Karyological investigation of four endemic Hyacinthella species from Turkey - Kiran, Yasar; Kilic, Selcuk; Dogan, Gulden; Eroglu, Hueseyin; Pinar, Sueleyman Mesut (Univ Tokyo Cytologia, 2024)
The chromosome numbers and karyotypes of four endemic species belonging to the genus Hyacinthella distributed in Turkey have been examined. These taxa encompass H. campanulata K. Perss. & Wendelbo, H. acutiloba K. Perss. & Wendelbo, H. siirtensis B. Mathew, H. micrantha (Boiss.) Chouard. The chromosome numbers of investigated taxa have been ascertained as 2n=2x= 18 (H. acutiloba and H. campanulata) and 2n=2x= 22 (H. micrantha and H. siirtensis). The mean chromosome length varies between 1.65 mu m (H. micrantha) and 6.37 mu m (H. siirtensis). Haploid chromosome lengths varied between 25.39 mu m (H. micrantha) to 31.56 mu m (H. siirtensis) among these species. The arm ratio was determined as a minimum of 1.06 in H. acutiloba, and as a maximum of 4.48 in H. siirtensis, whereas the lowest relative length was observed in H. siirtensis (6.08%), and the highest relative length was found in H. siirtensis (20.18%). Karyotype analysis indicated that Hyacinthella taxa typically possessed median (m), submedian (sm), and subterminal (st) chromosomes.
Keywords: Asparagaceae; Hyacinthella; Chromosome number; Karyotype; Turkey